CORRELATION BETWEEN LANGUAGE WORLDVIEW AND MENTAITY IN MODERN LINGUISTICS - V. S. Sosedova (Vestnik MGIMO-Universiteta)
The article is devoted to the correlation between concepts of mentality and language worldview in modern linguistics. Considering mentality within modern linguistics reflects the principle expansionism which consists in the fact that no science can remain within the borders of itself, it needs access to the adjacent areas of knowledge to produce the most comprehensive research. That is why linguistics is to use the data provided by such sciences as cultural studies, anthropology, sociology, etc. The paper highlights the main approaches to the issue of language worldview. The most relevant modern theory concerning the topic is the hypothesis of linguistic relativity in its weak form, which consists in the fact that language is only one of the factors that influence the way in which we conceptualize reality. Further in the article we put definitions of language worldview and give our own definition of the term. The part of the article dedicated to the mentality also provides definitions of the concept, indicates the relative novelty of studying the mentality of a nation within language sciences, it also provides a comparison of the given concepts. The author finds both similarities and differences and comes to the conclusion that, despite the apparent synonymy of the discussed concepts, there are important differences: they deal with different sides of world perception, they put emphasis on peculiar features of reality. Mentality is associated with the cultural aspect and the language worldview – with the liguocultural aspect. What is important is that both concepts are relevant to modern linguistics.